Efektivitas Layanan Bimbingan Kelompok Teknik Positive Reinforcement Berbasis Online Terhadap Peningkatan Minat Belajar Siswa Pada Era Covid-19 - Cindi Aprianti; Sofyan Abdi (Guidance : Jurnal Bimbingan dan Konseling, 2021)
The Effectiveness of Online-Based Positive Reinforcement Group Guidance Services on Increasing Student Interest in Learning in the Covid-19 Era (Experimental Study at SMK Pelita Alam Bekasi)". Guidance and Counseling Study Program, Faculty of Teacher Training and Education, As-syafiiyah Islamic University. The purpose of this thesis is to determine the effectiveness of group guidance services using online-based positive reinforcement techniques to increase student interest in learning during the Covid-19 era at SMK Pelita Alam Bekasi. The research method used in this research is quantitative with Quasi Experimental Designs research design, and the data analysis technique used is the Paired Sample T-test. This study has a population of 42 students. The determination of the sample in this study was carried out by using the type of non-probability sampling, with purposive sampling technique, so that the sample used in this study was 20 students with 10 members of the experimentl group and 10 members of the control class. Hypothesis test results show the Sig.2-tailed value of 0.022 <0.05 in the experimental class, and 0.034 <0.05 in the control class, which means that there is a difference in the average student interest in the pre-test and control classes. It can be concluded that Ha is accepted and Ho is rejected, this shows that online-based positive reinforcement group guidance services can increase student interest in learning in the Covid-19 era.